The Role of Innovation and Foreign Capital in Venture Capital Backed Investments: Empirical Evidence from Finland - Riikonen, Petrus (My University, 2022)
Venture capital (VC) has a significant impact for economic growth by acting as financial intermediate and provide funding to early-stage and innovative entrepreneurial firms. It is characteristics for the VC investments that they are including relatively high risks, and usually one or two of the portfolio companies are the ones making homerun for the whole fund. Due to small size of the target companies, it requires phenomenal growth up to billion dollar valuation for making the VC fund able to return the funds to its investors. That unique characteristic is the reason why VCs are mainly screening scalable and high-tech businesses, having ability to penetrate or even create new market segments. Academic literature has debated intensively about venture capital (VC) funds’ capability to generate significantly high returns. In historical period VC have been able to overperform the market constantly basis. Yet most of the literature have focused the VC value creation activities and their impact of the target firm operative performance. The purpose of this thesis is to examine value creation of venture capital investments in Finnish VC-backed transactions. Specifically, value creation is measured based on postinvestment firm performance from two point of views, (1) what is the role of innovation intensity and (2) foreign capital involvement in relation to improvement of financial performance of target companies over the investment period. This thesis utilizes the latest evidence from Finnish VC investments, and the data sample comprises 117 VC-backed Finnish firms, that have performed exits between the years 2005 and 2020. The evidence of value creation is hand collected from target companies’ financial statements post-investment. The empirical analysis consists of logistic regressions. The results show that an increase in innovation intensity has an increasing impact on the firm value measured in sales growth and enterprise value. However, the results indicate that VCs tend to invest in already innovative firms rather than accelerating the innovation intensity. In addition, relating to foreign VC involvement in the deal, results show that foreign VC involvement has been a significant impact on the increase in targets’ financial performance. However, in comparison to prior academic literature, we could not find that target’s development stages have an impact for the slope of financial performance improvement.
Keywords: venture capital; value creation; private equity investors; fi=Laskentatoimi ja rahoitus|en=Accounting and Finance|; Master's Degree Programme in Finance